The Role of University Scientist Mobility for Industrial Innovation - Ann-Kathrine Ejsing; Ulrich Kaiser; Hans Christian Kongsted; Keld Laursen (Institute for the Study of Labor (IZA), 2013)
Scientific knowledge is an important ingredient in the innovation process. Drawing on the knowledge-based view of the firm and the literature on the relationship between science and technology, this paper scrutinizes the importance of university scientists' mobility for firms' innovative activities. Combining patent data and matched employer-employee data for Danish firms, we can track the labor mobility of R&D workers from 1999 to 2004. We find that new joiners contribute more than long-term employees to innovative activity in the focal firm. Among new firm recruits, we observe that newly hired former university researchers contribute more to innovative activity than newly hired recent graduates or joiners from firms, but only in firms with a high level of absorptive capacity in the form of recent experience of hiring university researchers. We find also that firms' recent experience of hiring university researchers enhances the effect of newly hired recent graduates' contributions to innovation.
Keywords: O33; O34; C23; 330; innovative activity; science-technology relationship; labor mobility